Family Based Pedagogical Communication In The Context Of Transnational Family: The Kompas Pantura Model For Elementary School Children - Sulaeman, Dudung; Muryanto, Rusdiono (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Transnational families are a social phenomenon resulting from the global mobility of the workforce, which impacts the parenting and education patterns of elementary school-aged children. The physical absence of parents demands the presence of family pedagogical communication that is able to maintain learning support, internalization of values, and emotional attachment of children. This study aims to analyze the characteristics of family-based pedagogical communication in the context of transnational families and formulate a relevant conceptual model. The study used a qualitative approach with a critical literature study method based on current studies on transnational families, pedagogical communication, and elementary education. The results show that pedagogical communication in transnational families tends to be instructive, functional, and oriented towards academic control, while the dialogic and emotional dimensions are relatively weak. Dependence on digital media has not fully provided a meaningful pedagogical presence and has given rise to communication fragmentation and value inconsistencies. Therefore, a systematic and values-based pedagogical communication framework is needed. This study offers the KOMPAS–PANTURA Model as a conceptual alternative to strengthen transnational family pedagogical communication. The impact of this research is expected to enrich family pedagogical studies and child education practices in the era of global mobility.